OPTIMIZATION OF BIOCONVERSION OF WASTE COCONUT WATER TO ACETIC ACID - Enar, Rohmala
NIM : 20507059 Coconut water has sugar-content of 2.08 mg/l00g that was used as a raw material for acetic acid production. Coconut water that thrown away is a good source for environment pollution, since its Biological Oxygen Demand (BOD) around 40.000 mg/l. An attempt was made to reduce environment pollutant by transforming coconut water to acetic acid. This experiment can be used as a model to study the reaction in carbohydrate biotransformation. Two culture types were chosen as a starter that were Saccharomyces cerevisiae (laboratory [?LE2(803)] and market) and kamboucha.